IMPORTANCE OF RAPID ADAPTATION OF VALUE PROPOSITION TO THE CUSTOMER WANTS: A DYNAMIC CHANGE IN CUSTOMER WANTS DUE TO PANDEMIC OF COVID 19 - Baskoro, Gembong (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Pressures of pandemic Covid 19 and rapid technology development of Artificial Intelligence (AI), Big Data, Internet of Things (IoT), and IT based technology lead to the dynamic, sometimes unpredictable, change of customer wants. The dynamic change of customer wants may lead to unsustainable of business as customer has change the existing wants to the new ones. This situation becomes a pressure for business organizations because they have to have new information and update of the customer wants so that they can quickly adapt to their offered product and or business to customer. In the past, the process of updating customer wants may be done in several approaches whether regularly or based on input from the customer itself in the situation of normal business environment (offline). Nowadays, due to the pandemic of Covid 19, most of the customer relation should be done online, there is no other way. Therefore, it is difficult to really understand the customer wants in its reality. The wants, as in value proposition canvas, can be in term of pains and or gains and both of them hardly difficult to really capture via online. Consequently, the adjustment of product and or service to customer wants may delay or in the worst case there is no adaptation to the new wants. As a result, it may impact to the sustainability of the business as customer will of course seek to product and or service that meet the new wants. This paper will elaborate to ensure sustainability of the business by sharpening the linkage of value proposition to the customer wants. This paper will introduce the concept of (rapid) adaptation to capture the change of customer wants in the situation of pandemic of covid 19. This paper will also elaborate the what-if scenarios in the new normal era to ensure the change of customer wants can be captured so that improvement and or innovation to the product and or service can be done accordingly. Hopefully, this approach can improve the lack of matching between value proposition to customer wants. This paper will use experiential and case study method to develop the concept. Keywords: Business sustainability, Customer delight, Customer Wants, Value Proposition, Covid 19